PERAN PLH (PENDIDIKAN LINGKUNGAN HIDUP) SMA N 3 KLATEN ERA NEW NORMAL : BERTANAM DARI SEKOLAH MENUJU RUMAH - Vina NUR HIDAYAH; Fella Sufah Baedowi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
Adiwiyata school SMAN 3 Klaten applies Environmental Education to its students which is for better habits towards the environment in a sustainable manner. This cannot be realized in schools because of the emergence COVID-19. This study aims to determine the effect of Environmental Education on SMAN 3 Klaten students in New Normal era. The method used in this study uses a qualitative method with sampling techniques of data collection that is a random sample via Google Form on the students SMAN 3 Klaten. The result of this research is that SMAN 3 Klaten has implemented Environmental Education in New Normal era by learning from home, for example cultivating ornamental fish, cultivating medicinal plants and others. Environmental Education Students SMAN 3 Klaten while learning from the new normal era get innovations in the implementation of PLH not only in schools, students can plant at their house in New Normal era.